Molecular phylogenetics and taxonomy of Hypocenomyce sensu lato (Ascomycota: Lecanoromycetes): Extreme polyphyly and morphological/ecological convergence. Issue 5 (30th December 2018) - Bendiksby, Mika; Timdal, Einar
Abstract: We have addressed phylogenetic relationships and tested hypotheses about five presumed subgroups among 15 species of Hypocenomyce s.l. (including Pycnora ) by use of nuclear (ITS, LSU) and mitochondrial (SSU) ribosomal DNA‐regions. Bayesian, likelihood and parsimony phylogenetic analyses, of a dataset with broad Lecanoromycete taxon sampling, mostly support the five presumed subgroups, but two of these were found to be polyphyletic (the H. friesii ‐group and Pycnora ). The seven supported Hypocenomyce s.l. clades belong in different genera, families, orders and even subclasses, and represent a remarkable example of morphological and ecological convergence. Based on our molecular phylogenetic results, we split Hypocenomyce into four genera placed in two subclasses: (1) Carbonicola gen. nov. (Carbonicolaceae fam. nov., Lecanorales, Lecanoromycetidae; including C. anthracophila comb. nov., C. foveata comb. nov., and C. myrmecina comb. nov.); (2) Fulgidea gen. nov. (Umbilicariaceae, Umbilicariales, Umbilicariomycetidae subcl. nov.; including F. oligospora comb. nov. and F. sierrae comb. nov.); (3) Hypocenomyce (Ophioparmaceae, Umbilicariales; including H. australis, H. scalaris, and H. tinderryensis ; and (4) Xylopsora gen. nov. (Umbilicariaceae; including X. caradocensis comb. nov. and X. friesii comb. nov.). We split Pycnora into two genera: (1) Pycnora (Pycnoraceae fam. nov., Candelariales, "Candelariomycetidae"; including P. praestabilis, P. sorophora, and P. xanthococca ); and (2) Toensbergia gen. nov. (Sporastatiaceae fam. nov., unknown order, Lecanoromycetidae; including T. leucococca comb. nov.). We place Hypocenomyce isidiosa in Xylographa (Trapeliaceae, Baeomycetales, Ostropomycetidae; X. isidiosa comb. nov.). We place the family Ophioparmaceae in the Umbilicariales. Our type studies have shown that the epithet " myrmecina " should replace " castaneocinerea ", and lectotypes are chosen for Lecidea friesii Ach., L. scalaris var. myrmecina Ach., Psora cladonioides var. albocervina Räsänen, and P. cladonioides var. castaneocinerea Räsänen. Elixia cretica is reported as new to North America (from Mexico) and Australia.